Determination of pseudo‐ginsenoside GQ in human plasma by high performance liquid chromatography–tandem mass spectrometry. (15th July 2013) - Huo, Jiping; Wang, Hongyun; Hu, Pei; Li, Pingya; Liu, Jinping; Jiang, Ji
ABSTRACT: A specific, sensitive and rapid method based on high performance liquid chromatography coupled to tandem mass spectrometry (HPLC‐MS/MS) was developed for the determination of pseudo‐ginsenoside GQ in human plasma. Liquid–liquid extraction was used to isolate the analyte from biological matrix followed by injection of the extracts onto a C8 column with isocratic elution. Detection was carried out on a triple quadrupole tandem mass spectrometer (API‐4000 system) in multiple reaction monitoring mode using negative electrospray ionization. The mobile phase consisted of methanol–10 mm ammonium acetate (90:10, v/v) and the flow rate was 0.3 mL/min. The method was validated over the concentration range of 5.0–5000.0 ng/mL for plasma. Inter‐ and intra‐day precisions (relative standard deviation) were all within 15% and the accuracy (relative error) was ≤9.4%. The lower limit of quantitation was 5.0 ng/mL. The pseudo‐ginsenoside GQ was stable after 8 h at room temperature, 24 h at autosampler and three freeze–thaw cycles (from −30 to 25 °C). The method was successfully applied to the pharmacokinetic study of pseudo‐ginsenoside GQ in healthy Chinese volunteers. Copyright © 2013 John Wiley & Sons, Ltd.